KUALITAS PELAYANAN BELLBOY DI FOX HOTEL PEKANBARU - Hesti Norfadillah; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Hotel is a commercial business that open for public, Front Office Departement is one of the most important part in hotel operational because in many occasions at hotel in providing rooms and guest needs especially in the bellboy section, so it requires an adequate many of bellboy and with good service but what often happens bellboy who serves guest is not accordance with the many of guest come at hotel. Resulting in service quality that is not accordance with the many of employees work. The purpose of this study are: (1) Describe the quality of service bellboy at the Fox Hotel Pekanbaru, (2) to describe the satisfaction of the guests at the Fox Hotel Pekanbaru  and (3) analyze the relationship between service quality with guest satisfaction bellboy at the Fox Hotel Pekanbaru. This type of research is correlational. The population is all guests who stayed at Fox Hotel Pekanbaru. The method used is non propability insedental sampling technique sampling with a sample of 100 people. The results showed that: (1) Quality of service bellboy are in the very good category (97%), (2) Guest Satisfaction are in the very good category (96%) and (3) There is a relationship that is positive and significant correlation between quality of service bellboy with guest Keywords: Service Quality, Bellboy, Fox Hotel pekanbaru